REVEAL OF CERTAIN ADIPOKINES (ADIPONECTIN AND LEPTIN) AND PHYSIOLOGICAL PARAMETERS LEVELS IN WOMEN WITH INFERTILITY - AlSadoon, Asawer Kareem (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Adipose tissue produces adipokines, and adipocytes have an impact on the reproductive organs through the production of adiponectin and leptin. Therefore, it is essential to evaluate adipokines and sex hormones in order to have a deeper understanding of infertility. Thus, the goal of the current study was to assess adipokines and biochemical markers in infertile patients. In this study, 65 women between the ages of 17 and 40 years old (mean: 27.8±4.08 years) were included. All were consecutively admitted to the clinic at AL-Kut Hospital for Gynecology Obstetrics and Pediatrics (infertility center) at February to May 2024. All women had infertility as diagnosed by the physician. also, this study including 40 healthy women as control group. The results showed that the concentrations of follicle stimulating hormone (7.42±0.13) and luteinising hormone (LH) (7.13±0.25) in serum of infertility women indicated a significant (P <0.05) rise in contrast to healthy women (5.037.42±0.29; 3.657.42±0.16). The levels of MDA (1.93±0.11) demonstrated significant (P <0.05) increase and GSH (0.371±0.027) decreased in infertility women compared with healthy women (1.22±0.09; 0.441±0.014). Adiponectin concentration in serum of infertility patients (4.55±0.19) indicated non-significant (P <0.05) variations in contrast to healthy women (4.61 ± 0.23). the concentration of leptin indicated a significant (P <0.05) rise in infertility women (14.83 ±1.92) in contrast to healthy women (5.48 ±0.41). It is concluded from the study that there was also an imbalance in the case of oxidative stress. On the other hand, it was noted that there is a correlation between leptin levels and infertility in women